v.8 - "Keynes, John Maynard" (New Delhi, 2013)
Originally written as a Fellowship Dissertation for King's College, Cambridge, between 1906 and 1909, Keynes's Treatise represents his earliest large-scale writing. Rewritten for publication during 1909-12 and 1920-1, it was the first systematic work in English on the logical foundations of probability for 55 years. As it filled an obvious gap in the existing theory of knowledge, it received an enthusiastic reception from contemporaries on publication. Even today amongst philosophers, the essence of Keynes's approach to probability is established. This edition reprints, with Keynes's own corrections, the first edition of the Treatise. An introduction by Professor Richard Braithwaite, formerly Knightbridge Professor of Moral Philosophy in Cambridge and a close friend of Keynes from the time he was finishing this book, sets Keynes's ideas in perspective.
Keywords: Keynesianism